Baseline Design and Performance Analysis of Laser Altimeter for Korean Lunar Orbiter - Hyung-Chul Lim; Gregory A. Neumann; Myeong-Hwan Choi; Sung-Yeol Yu; Seong-Cheol Bang; Neung-Hyun Ka; Jong-Uk Park; Man-Soo Choi; Eunseo Park (Journal of Astronomy and Space Sciences, 2016)
Korea’s lunar exploration project includes the launching of an orbiter, a lander (including a rover), and an experimental orbiter (referred to as a lunar pathfinder). Laser altimeters have played an important scientific role in lunar, planetary, and asteroid exploration missions since their first use in 1971 onboard the Apollo 15 mission to the Moon. In this study, a laser altimeter was proposed as a scientific instrument for the Korean lunar orbiter, which will be launched by 2020, to study the global topography of the surface of the Moon and its gravitational field and to support other payloads such as a terrain mapping camera or spectral imager. This study presents the baseline design and performance model for the proposed laser altimeter. Additionally, the study discusses the expected performance based on numerical simulation results. The simulation results indicate that the design of system parameters satisfies performance requirements with respect to detection probability and range error even under unfavorable conditions.